Roma e i Romani da una prospettiva antiochena - Neri, Valerio Lieto (Tesserae iuris, 2023)
The subject of the work is the analysis of the attitude towards the city of Rome and the Romans by the two intellectual leaders of the city of Antioch in Syria in the fourth century AD, in the pagan and Christian field, Libanius and John Chrysostom. Libanius, of Antiochian origin, was for many years, until his death, a professor of rhetoric in his city and was also an important figure in the political sphere, especially under the emperor Julian. John Chrysostom, also of Antiochian origin, was a pupil of Libanius before his conversion to Christianity and his long activity as a presbyter appointed by the bishop to preach in the city. Both have never been at Rome and have only indirect knowledge of the ancient capital. Libanius had correspondence with personalities who lived in Rome and even with exponents of the Roman aristocracy, such as Quintus Aurelius Simmachus, and, in all probability, with the greatest historian, of Antiochian origin, of late antiquity, Ammianus Marcellinus, John Chrysostom is interested in Rome especially as the theater city of the preaching and death of the two great apostles Peter and Paul, coming from Antioch, and of the bishop of the city Ignatius, who suffered martyrdom in Rome, before his relationship with Pope Innocent, during the troubled period of his bishopric in Constantinople